The Effect of Urea on Aggregation and Incubation Resistance of Human Platelets - Reuter, H; Linker, H (Thrombosis and Haemostasis, 1969)
Investigations have been carried out to study the effect of urea on aggregation and incubation resistance of human platelets. Urea in high concentrations inhibits the Ca++-induced aggregation in platelet-rich EDTA-plasma while at low concentrations an increased aggregation takes place. Incubation of platelet-rich plasma at 37° C in the absence of divalent cations was performed in the presence and absence of 0.1 M urea. The temperature-induced percentage inhibition of aggregation was found to be significantly lower in the presence of urea.